The Role of Financial Literacy on Investment Decisions in Supporting Agricultural Development: What is the Future Agenda? - Murini Murini; Arifuddin Mas’ud (Journal of Global Innovations in Agricultural Sciences)
Financial literacy is recognized as a useful tool for making financial decisions. The better a person's literacy, the better their financial management including in making investment decisions, including farmers. This study aims to uncover a future agenda to investigate the role of financial literacy in shaping investment decisions for farmers which is very useful in business development and agricultural development in general. The next goal is to present empirical evidence as an agenda for further investigation into human resource management practices. They use a literature review study approach with a systematic review paradigm. Involving around 38 major journals that discuss financial literacy and investment decisions in the agricultural sector, supported by other journals that discuss resource management practices. The analysis results show that the study analyzes the role of financial literacy in shaping investment decisions for farmers and agricultural development in 16 countries, spread across Asia, Africa, and Europe. The agenda for discussing future research that interests researchers is focused on four things. First, factors that influence/drive investment decisions. Second, factors that shape financial literacy in agricultural business development. Third, household finances. Fourth, is the level of financial literacy. Specifically, human resource management practices that need to be further proven are regarding financial literacy, cognitive bias, and emotional bias in reflecting investment decision-making. Theoretical implications are that financial literacy has been proven to contribute to shaping the knowledge of the community (farmers and business actors) when making investment decisions. To strengthen this, further evidence is needed, along with factors that influence (including barriers) financial literacy. Farmer households are the most frequently suggested subjects. Practical implications are that the Government and other parties involved in financing agricultural businesses must participate in providing scenarios and infrastructure (technology and innovation) to support financial literacy for farmers and the general public. Keywords: Financial literacy, decision making, investment, farmers, farmer household, human resource management, review, future agenda.